1979
DOI: 10.1288/00005537-197906000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy‐related subglottic stenosis: Bacteriologic pathogenesis

Abstract: Subglottic stenosis carries devastating consequences. Its pathogenesis, and therefore prevention, have thus far eluded precise definition. The following data suggest that tracheostomy results in a contaminated wound, secondarily infecting a larynx which may have been injured by prior intubation, fracture, or surgery. The interpretation of these data is based upon the tested assumption that infection prolongs healing of injured tissue and predisposes to scar and stricture formation. Therefore, the ability of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(78 citation statements)
references
References 14 publications
3
73
0
2
Order By: Relevance
“…[14][15][16]23 In a dog model, trauma alone was insuffi cient to induce granulation tissue, but trauma and bacterial contamination led to granulation tissue. 15 Human studies have shown an association between positive cultures and the presence of granulation tissue, 14,16,23 and airway build-up. Whether this coating affects infection rates warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16]23 In a dog model, trauma alone was insuffi cient to induce granulation tissue, but trauma and bacterial contamination led to granulation tissue. 15 Human studies have shown an association between positive cultures and the presence of granulation tissue, 14,16,23 and airway build-up. Whether this coating affects infection rates warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that different stent types would have different incidence rates of infection and that infection would lead to the development of granulation tissue. [14][15][16] …”
Section: Infectionmentioning
confidence: 99%
“…[20][21][22][23][24][25] An extended ICU stay increases risk to nosocomial infection and increases the economic burden to the healthcare system. Alternatively, there can be significant risk associated with early MDO intervention in neonates during their first days of life.…”
Section: Discussionmentioning
confidence: 99%
“…High insertion of the cannula between the cricoid cartilage and the first tracheal ring, and oblique insertion with the possibility of erosion and fracture of the cricoid ring are risk factors [101,154,158,160]. Other risk factors include damage of the cricoid ring by prolonged translaryngeal intubation before the tracheal cannula has been installed or infection [150,157,166].…”
Section: Tracheal Stenosismentioning
confidence: 99%